2017
DOI: 10.18632/oncotarget.19153
|View full text |Cite
|
Sign up to set email alerts
|

Silibinin: an old drug for hematological disorders

Abstract: IntroductionSilibinin (silybin), a non-toxic natural polyphenolic flavonoid, is the principal and the most biologically active component of silymarin. It is efficient in the treatment of acute and chronic liver disorders caused by toxins, drug, alcohol, hepatitis, and gall bladder disorders. Further, in our previous studies, we explored the anti-cancer efficacy in common cancers, such as lung, prostatic, colon, breast, bladder, as well as, hepatocellular carcinoma. Interestingly, silibinin is still not solely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…Silibinin, a non-toxic polyphenolic flavonoid, is the main active component extracted from a medicinal plant named Silybum marianum 64 . It was previously reported that silibinin has anti-inflammation, antifungal, antioxidant and antitumor activities 38 - 44 , 46 , 47 , 65 - 67 .…”
Section: Discussionmentioning
confidence: 99%
“…Silibinin, a non-toxic polyphenolic flavonoid, is the main active component extracted from a medicinal plant named Silybum marianum 64 . It was previously reported that silibinin has anti-inflammation, antifungal, antioxidant and antitumor activities 38 - 44 , 46 , 47 , 65 - 67 .…”
Section: Discussionmentioning
confidence: 99%
“…A medicinal plant Silybum marianum was commonly used as a hepatoprotective medication to treat jaundice and enlarged liver and spleen 17. Silibinin (Silybin) (Figure 1A), a non-toxic polyphenolic flavonoid, is the main biologically active component extracted from S. marianum 18. It was reported that silibinin has anti-inflammation, antifungal, antioxidant, and anti-cancer effect 1922.…”
Section: Introductionmentioning
confidence: 99%
“…These effects were demonstrated and mediated by its antioxidative, radical-scavenging, others specific receptors interaction, and the modulation of various cell-signaling pathways, including NF-κ B, targeting of STAT3, inhibition of EGFR-MAPK/ERK1/2 signaling, activity upon Rb and E2F proteins, IGF-receptor signaling, etc. [24,[27][28][29]. Various preclinical studies have shown that silibinin can inhibit lung, breast, gastric, prostate, and skin cancer [20,21], but this does not reflect in the pilot trials performed in humans to date.…”
Section: Introductionmentioning
confidence: 99%